Assessment of the level of anxiety of caring for disabled - Mess, Eleonora Anna; Rybakiewicz, Alice; Pawelak, Agnieszka; Lisowska, Aleksandra; Ornat, Maciej (Journal of Education, Health and Sport, 2019)
Admission: Care for disabled child may present many difficulties and cause stressful situations that generate negative emotions. One of them is fear.Objective of the work: Assessment of the level of anxiety state and trait in people taking care of a disabled child.Materials and methods: The study was conducted among 100 employees center for disabled children and Wierzbice in Katy Wroclawskie. The research tool was the Inventory and the State Trait Anxiety (Iscle).Results: The level of anxiety carers of people with disabilities depends on the age of the subjects (p = 0.025), professional experience (p = 0.047), operating system (0.002) and the degree of disability of children (p = 0.004). While the intensity of the drug is not affected by gender, education and occupation.Discussion:Both the age and experience of the work associated with sophistication and getting used to disability beneficiaries. The impact may also have a stable position in the life of the elderly. The importance of the degree of disability is unmistakable, taking into account both the physical stress and emotional caregivers.